FROM RITUAL TO DIGITAL INTERACTION: RETHINKING MUZAKKI ENGAGEMENT THROUGH INSTITUTIONAL DA’WAH INNOVATION (MDDI) IN THE SOCIETY 5.0 ERA - Ivana Deviyanti; Rio Apandi; Sumaryati Sumaryati (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2026)
This research aims to find out how waqf management is carried out at the Darunnajah Islamic Boarding School in the context of developing Islamic Education Institutions. The research was carried out using a qualitative methodology approach, where researchers examined documents, made observations and interviewed relevant parties. The data collected was then analyzed descriptively, analytically and reflectively. This research suggests that waqf is a voluntary gift made by Islamic people for the purpose of developing Islamic society. Waqf is a form of worship that is highly recommended not only for individual relationships with God, but also for relationships between humans on this earth. Moreover, waqf can be developed in such a way as to be used as well as possible in accordance with the rules of the Islamic religion. The Darunnajah Islamic Boarding School, which was founded in 1942, has carried out waqf management with a strategic approach that is relevant to developing the resources of the Islamic Education Institution. It is hoped that the waqf management strategy at the Darunnajah Islamic Boarding School in Jakarta can be developed better so that the benefits of waqf can be felt by students, society, and the Indonesian nation.